Research on variable pairing scheme for V/f controlled MMC station - Ma, Junchao; Wu, Zhe; Sun, Ke; Wang, Chenxu; Lu, Chengyu; Gu, Yilei; Liu, Jianing; Zhu, Chengzhi; Guo, Hanlin; Zhang, Zheren; Xu, Zheng (Frontiers in Energy Research, 2024)
The grid-forming control is a promising solution for renewable power integration. In this paper, the variable pairing scheme for the voltage controller of grid-forming modular multilevel converter (MMC) in islanded network with synchronous machine is studied, based on V/f control which is a special type of grid-forming control. According to the concept of the relative gain array (RGA), it is found out that RGA matrix can be derived based on steady-state sensitivity analysis. Then, the steady-state characteristics of typical electrical components in the islanded network are considered, and the analytical expression for calculating the RGA matrix is derived. Based on a typical system, a variable pairing scheme is suggested by the calculated RGA matrix elements. The time-domain simulation is carried out in PSCAD/EMTDC, and the simulation results verify feasibility and the advantage of the suggested variable pairing scheme.